Chronic Obstructive Pulmonary Disease Exacerbation Complicated with Pneumonia and Lung Cancer: An Evidence-based Case Report of Erdosteine Role in the Management of Complex COPD - Ilham, Ahmad Fadhil; Rakasiwi, Muhammad Ilham Dhiya; Felim, Ris Raihan; Arfan, Ahmad; Burhan, Erlina (Malang Respiratory Journal, 2024)
Background: Acute exacerbations of chronic obstructive pulmonary disease (COPD) are strongly associated with poor health status and morbidity. Erdosteine is a mucolytic agent that also has anti-inflammatory, antioxidant and antibacterial effects. This case report aims to evaluate the role of erdosteine in the prevention and treatment of acute exacerbations of complex COPD case. Case: A 73-year-old male arrived at the emergency department with an increased difficulty in breathing that had deteriorated over the previous 5 days, and had a history of heavy smoking for more than 40 years. Following a thorough examination, he was diagnosed with acute exacerbation of COPD (Anthonisen criteria type 2) in clinical group E, pneumonia, along with stage IIIA right lung tumor (T4N1Mx), and received erdosteine inhalation as part of his treatment. Discussion: A comprehensive search of journal databases (PubMed, EMBASE, CENTRAL, EBSCO Medline, Scopus, and ProQuest) was conducted using specific keywords, critical appraisal based on the Oxford Center for Evidence-Based Medicine. Article selection resulted in 1 systematic review article for the prevention of acute exacerbations and 1 systematic review article for the management of acute exacerbations of COPD. In patients with stable COPD, administration of erdosteine in the standard COPD regimen significantly reduced the risk of exacerbations (RR=0.65; p=0.01), while in patients with acute exacerbations of COPD, erdosteine increased treatment success (OR=3.2; p<0.0001). Conclusion: Erdosteine may serve as a therapeutic choice for COPD patients in preventing or managing acute exacerbations.